Study of Mechanical Behavior of Expansive Clay due to the Addition of Nano Silica Dioxide (SiO2) - Hirwo, N.T.; Pratikso, Pratikso; Karlinasari, R. (ASTONJADRO, 2025)
Expansive clay which is a problematic soil is spread almost all over the world, including Indonesia. In various regions in Indonesia, expansive clay has damaged the infrastructure above, causing high maintenance costs. Expansive clay often becomes a problem when infrastructure is built on it, due to its large swell and shrink properties. Improved stabilization of expansive clay is required to improve mechanical behavior (shear strength, compressive strength and modulus of elasticity). In this study, the effect of increasing shear strength, unconfined compressive strength and modulus of elasticity of expansive clay added with SiO2 nano material will be investigated. SiO2 nanomaterial can be produced from processing waste from geothermal power plants. The percentage of SiO2 nanomaterial mixture used in this research is 0%; 1%; 2% and 3% compared to dry soil weight. The increase in shear strength, unconfined compressive strength and modulus of elasticity will affect the mechanical behavior of expansive soil. This increase in mechanical behavior also means increasing the bearing capacity of the soil and this is very influential in stabilizing expansive clay. From laboratory substantiation that have been carried out, the laboratory test results show an increase in modulus of elasticity of 17%. An increase in shear strength of 64% and an increase in UCS stress of 91%, which occurs at the optimum mixing nano SiO2 ratio.